Do closeness, support, and reciprocity influence trust in friendship? - Muh Reza Firmansyah; Faturochman Faturochman; Wenty Marina Minza (Fakultas Psikologi Universitas Indonesia dan Ikatan Psikologi Sosial-HIMPSI, 2021)
Prior qualitative research by Faturochman and Minza (2014) on trust in Indonesia found that trust is influenced by relational attributes, including closeness, support, and reciprocity. This study aims to examine whether the findings of the previous research can be applied in specific forms of relationships, e.g. friendship. The survey method is used in this study, involving 97 males and 123 (N = 220) females who completed a scale related to the variables studied. We found that support and reciprocity significantly predicted the score of trust. However, closeness did not. It was also found that the effect of support is higher than reciprocity. Based on the research, we created the regression model with the contribution of support to the trust 37.8%, then reciprocity addition which was analyzed together with support gave a total contribution to the trust 41.5%. The implication of this study is further discussed.